Hitler attacks Pearl Harbor : why the United States declared war on Germany - Hill, Richard F. (Boulder, Co. : L. Rienner, 2002)
ill theorizes that the diplomatic community opened the European theater to a full-scale war on Germany because Hitler's pressure on his Japanese allies caused the Pearl Harbor attack.
Includes bibliographical references (p. 215-222) and index.
Keywords: World War, 1939-1945 -- Diplomatic history; National socialism; National security -- United States